Comprehensive analysis of m5C-Related lncRNAs in the prognosis and immune landscape of hepatocellular carcinoma - Lu, Qian; Liu, Lianyu; Wang, Shuai; Zhang, Qi; Li, Li (Frontiers in Genetics, 2022)
5-Methyladenosine (m5C) is a type of epigenetic modification involved in the progression of various cancers. To investigate the role of m5C-related long non-coding RNAs (lncRNAs) in the prognosis and immune cell infiltration in hepatocellular carcinoma (HCC), we obtained patients’ clinical information and transcriptome data of HCC from the Cancer Genome Atlas (TCGA) database. We applied Pearson correlation analysis to construct an m5C-related lncRNA–messenger RNA (mRNA) co-expression network. Univariate Cox analysis, least absolute shrinkage and selection operator (LASSO), and multivariate Cox analysis were employed to establish an m5C-related lncRNA prognostic risk model. We then verified the model using Kaplan–Meier analysis, principal component analysis, as well as univariate and multivariate Cox analyses. The expression of m5C-related lncRNAs was validated in HCC tissues and different cell lines. Combining the risk score and clinicopathological features, a nomogram was established for predicting the overall survival (OS) of HCC patients. Furthermore, gene set enrichment analysis (GSEA) revealed that some tumor-associated pathways were significantly enriched in the high-risk group. Immune cell infiltration analysis demonstrated that the levels of Treg cells, neutrophils, and M2 macrophages were higher in the high-risk group. In addition, patients with high tumor mutation burden (TMB) had worse OS than those with low TMB. We also assessed the immune checkpoint level and chemotherapeutic agent sensibility. Then in vitro experiments were performed to examine the biological function of MKLN1-AS in HCC cells and found that knockdown of MKLN1-AS suppressed the proliferation, migration, and invasion. In conclusion, m5C-related lncRNAs played a critical role in predicting the prognosis of patients with HCC and may serve as new therapeutic targets for HCC patients.